(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze volume variation, untouched walls, transportation, and centralization in long oval canals prepared with ProTaper Next (PTN), X File (XF) and X Gray (XG) by microcomputed tomography (micro-CT). Forty-five lower incisors were divided into three groups (PTN, XF and XG) with 15 specimens each, according to the micro-CT pre-instrumentation (PI) analysis. After the use of each instrument new exams were performed. Volume variation and untouched walls data were analyzed by two-way ANOVA, and for the first one, Tukey HSD or Games-Howell tests were applied in the sequence; data of transportation and centralization were compared by Kruskal-Wallis and Mann-Whitney test. The statistical significance was set at p < 0.05. Between thirds, higher wear values were found in the cervical (p <0.001). PI and the instrument X3 (30/.07) differed in all systems (p < 0.05). No significant difference concerning the percentage of untouched walls between the systems occurred (p = 0.836), while the degree of transportation and centralization was similar between then, with p values of 0.531 and 0.155, respectively. However, between thirds, significant difference was found (pc = 0.029), with the middle third presenting superior centralization than the apical (p = 0.010). In conclusion, PTN, XF and XG had similar results in the shaping ability, transportation, and centralization of long oval canals.